The Sound of Memory: Acoustic Conflict and the Legacy of the French Wars of Religion in Seventeenth-Century Montpellier. Issue 1 (2nd January 2019) - van der Linden, David
Abstract : This article explores the commemorative meaning of sound in early modern Montpellier, focusing on the use of processional music and church bells to remember the French Wars of Religion. Scholarship has demonstrated that music in post-Reformation Europe often served to consolidate confessional identities, but this article argues that in religiously mixed communities like Montpellier, sound also served as a memory vector. In the wake of the French religious wars, Protestants and Catholics developed competing soundscapes that revived painful memories about the wars and sustained religious tension throughout the seventeenth century. Catholics relied on frequent processions to recall the destruction of their churches and monasteries at the hands of the Protestants, and chose specific songs to underline their triumph in re-establishing Catholic worship. The memory of losing their church bells also prompted them to fight Protestant attempts at installing their own bells after the wars. On the basis of untapped archival sources, this article also reconstructs the musical culture of Catholics in seventeenth-century Montpellier, paying particular attention to the cathedral chapel and the confraternity of White Penitents. *